Adventitial Fibroblasts Release Interleukin 6 After Vascular Injury and Induce Smooth Muscle Cell Proliferation and Neointima Formation - Jochen Dutzmann; Jan‐Marcus Daniel; Laura Korte; Frederik J. Kloss; Kai Knöpp; Katrin Kalies; Kevin J. Croce; Thomas J. Herbst; Barbara Huibregtse; Felix J. Vogt; Stefan Offermanns; Johann Bauersachs; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Vascular restenosis resulting from neointima formation significantly limits the efficacy of percutaneous interventional therapies compared with bypass surgery. The adventitial layer is involved in neointima formation, but the detailed pathophysiological interplay of the different cell types in this process is still unclear. Methods We analyzed the correlation between adventitial and neointimal tissue size in human postmortem restenotic lesions after angioplasty. In porcine and mouse models of vascular injury, we examined early proliferation of fibroblasts and adventitial expansion. Using anti‐CD45 antibodies, we identified recruited leukocytes as the source of fibroblast activation following vascular injury in mice. A time‐course experiment on neointima formation demonstrated that adventitial activation precedes the proliferation of medial and neointimal smooth muscle cells (SMCs). To further investigate this process, we developed a mouse model enabling the surgical removal and transplantation of adventitial tissue. Results We observed that activated adventitial fibroblasts release interleukin 6 and other cytokines, which strongly induce SMC proliferation and migration in vitro. In interleukin 6 knockout mice, supernatants from activated adventitia grafts failed to stimulate SMC proliferation and migration. Furthermore, transplantation of adventitial grafts from interleukin 6 knockout mice did not induce neointima formation. Cell fate tracking experiments using double transgenic reporter mice demonstrated that resident adventitial cells do not directly contribute to the neointimal cellular mass. Instead, medial SMCs were identified as the primary source of neointimal cells. Conclusions We show that the release of interleukin 6 by adventitial fibroblasts induces the subsequent proliferation and migration of medial SMC in the process of neointima formation. Thus, we propose a new paradigm for adventitial fibroblasts in this process as a paracrine inflammatory engine. Anti‐inflammatory targeting of the vascular adventitia might thus be promising to limit neointima formation.